Understanding Quorum-Sensing and Biofilm Forming in Anaerobic Bacterial Communities - Markowska, Kinga; Szymanek-Majchrzak, Ksenia; Pituch, Hanna; Majewska, Anna (International journal of molecular sciences, 2024)
Biofilms are complex, highly organized structures formed by microorganisms, with functional cell arrangements that allow for intricate communication. Severe clinical challenges occur when anaerobic bacterial species establish long-lasting infections, especially those involving biofilms. These infections can occur in device-related settings (e.g., implants) as well as in non-device-related conditions (e.g., inflammatory bowel disease). Within biofilms, bacterial cells communicate by producing and detecting extracellular signals, particularly through specific small signaling molecules known as autoinducers. These quorum-sensing signals are crucial in all steps of biofilm formation: initial adhesion, maturation, and dispersion, triggering gene expression that coordinates bacterial virulence factors, stimulates immune responses in host tissues, and contributes to antibiotic resistance development. Within anaerobic biofilms, bacteria communicate via quorum-sensing molecules such as N-Acyl homoserine lactones (AHLs), autoinducer-2 (AI-2), and antimicrobial molecules (autoinducing peptides, AIPs). To effectively combat pathogenic biofilms, understanding biofilm formation mechanisms and bacterial interactions is essential. The strategy to disrupt quorum sensing, termed quorum quenching, involves methods like inactivating or enzymatically degrading signaling molecules, competing with signaling molecules for binding sites, or noncompetitively binding to receptors, and blocking signal transduction pathways. In this review, we comprehensively analyzed the fundamental molecular mechanisms of quorum sensing in biofilms formed by anaerobic bacteria. We also highlight quorum quenching as a promising strategy to manage bacterial infections associated with anaerobic bacterial biofilms.